(untitled) (Web of Teachers: Inderscience Research, 2024)
This article focuses on complex problems encountered in the translation process, in particular grammatical issues. It offers a careful study of the available literature, provides various methods used to solve these problems, provides empirical results of Applied Research, participates in a critical discussion and concludes with proposals to improve the quality of translation.